Diagnostic markers and prognostic factors in thyroid cancer. (October 2009) - Vriens, Menno R; Schreinemakers, Jennifer MJ; Suh, Insoo; Guerrero, Marlon A; Clark, Orlo H
There has been considerable progress identifying biomarkers in thyroid tumors that improve the accuracy of fine-needle aspiration biopsy and also help predict tumor aggressiveness or behavior. In this review we address both the clinical potential of molecular biomarkers and their usefulness, based on the most recent literature. We describe the current best clinical staging systems and the common somatic mutations in thyroid cancer. The BRAF mutation is the most common mutation in papillary thyroid cancer and has recently been reported to be associated with disease aggressiveness; it is also an independent predictor of tumor behavior. Combined testing of RET/PTC, NTRK, RAS and PAX8––PPAR γγ, which are mutually exclusive mutations, helps improve the accuracy of fine-needle aspiration biopsy. Gene-expression profiling studies have identified a variety of potential molecular markers to help distinguish benign from malignant thyroid neoplasms. Expression analysis of differentially expressed microRNAs also appears to be a promising diagnostic approach for distinguishing benign from malignant thyroid neoplasm. It is especially useful for indeterminate nodules by fine-needle aspiration biopsy.